Prevalence of anti-dense fine speckled 70 antibodies in healthy individuals and patients with antinuclear antibody-associated autoimmune rheumatic diseases in Japan. Issue 9 (5th March 2021) - Hayashi, Nobuhide; Uto, Kenichi; Imanishi, Akiko; Sugiyama, Daisuke; Morinobu, Akio; Saegusa, Jun
Abstract : Abstract: Previous studies from various countries have reported anti-dense fine speckled pattern (DFS)70 antibody prevalence but few studies have been from Asia. We investigated the prevalence of anti-DFS70 autoantibodies in a Japanese cohort of healthy individuals (HI) and patients with antinuclear antibody-associated autoimmune rheumatic diseases (AARD). Enzyme-linked immunosorbent assay and indirect immunofluorescence were performed using samples from 250 HI and 276 AARD patients. The overall anti-DFS70 antibody prevalence in HI was 16.4%, with 12.8% for males and 20.0% for females (sex difference; P = .12). In AARD patients, the anti-DFS70 antibody prevalence in systemic lupus erythematosus, mixed connective tissue disease, systemic sclerosis, dermatomyositis and polymyositis (DM/PM), Sjögren syndrome, and rheumatoid arthritis (RA) was 22.1%, 14.3%, 14.3%, 3.0%, 21.3%, and 18.1%, respectively (no significant difference between AARD patients except DM/PM and HI). The prevalence of isolated anti-DFS70 antibody in HI and all AARD patients excluding RA was 14.8% (37/250) and 4.4% (9/204), respectively ( P < .01 vs HI). Among anti-DFS70 antibody-positive cases, 63.4% (26/41) were DFS pattern by IIF and 23.5% (8/34) were HI and AARD patients excluding RA, respectively. The anti-DFS70 antibody prevalence in HI and AARD patients in Japan was similar. Furthermore, the anti-DFS70 antibody prevalence in HI and AARD in Japan is higher than in HI and AARD in regions other than Asia. This makes AARD differential diagnosis by antinuclear antibody screening difficult.